2019
DOI: 10.1186/s41039-019-0108-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect on new knowledge and reviewed knowledge caused by the positioning task in closed concept maps

Abstract: The advancement of technology has made it possible for automated feedback to be added to learning activities such as the construction of concept maps. The addition of feedback allows learners to acquire new knowledge instead of only focusing on reviewed knowledge. The cognitive processes for acquiring new knowledge and reviewing knowledge are different, so the benefits of concept maps in past research may not apply to the acquisition of new knowledge. However, how concept map construction varies across these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
(47 reference statements)
1
3
0
Order By: Relevance
“…The extended map activity encourages students to integrate newly learned information with existing cognitive structures and achieve new knowledge. In knowledge construction, the learner does not merely recall the material but also transfers previous experience to solve new problems (Furtado et al, 2019;Mayer, 2002;Prasetya et al, 2022;Xu, 2022). This study proves that achieving ER scores on EKB positively impacts students' comprehension.…”
Section: Research Questionsupporting
confidence: 55%
“…The extended map activity encourages students to integrate newly learned information with existing cognitive structures and achieve new knowledge. In knowledge construction, the learner does not merely recall the material but also transfers previous experience to solve new problems (Furtado et al, 2019;Mayer, 2002;Prasetya et al, 2022;Xu, 2022). This study proves that achieving ER scores on EKB positively impacts students' comprehension.…”
Section: Research Questionsupporting
confidence: 55%
“…The score of the students' concept map component is evaluated based on a comparison with the concept map expert (Furtado et al, 2019). The material organization refers to the characteristic of Marchantiophyta by Glime (2006).…”
Section: Methodsmentioning
confidence: 99%
“…Comparing the teacher concept map with student concept maps could portray students understanding regarding the materials [20]. Kit-Build concept map has been practically used in several kinds of learning environment and studies about Kit-Build showed its positive impact towards students understanding [12,13] and memory retention [5,6].…”
Section: Kit-build Concept Map and Its Concept Map Authoring Systemmentioning
confidence: 99%
“…Concept map has been long used to support meaningful learning [1][2][3] and helped students to understand concepts better, develop critical thinking and problemsolving skills [4]. Using concept maps in learning environment is effective to promote not only meaningful learning, but also memory retention of students; it has been confirmed in several studies [5][6][7]. Meaningful learning could also be attained in cooperative learning [8] by collaboratively constructing knowledge, exchanging ideas, embodying one's understanding, or sharing past experiences in the forms of concept maps.…”
Section: Introductionmentioning
confidence: 97%